A C-terminal fragment of adhesion protein Fibulin7 regulates neutrophil migration and functions and improves survival in LPS induced systemic inflammation. (July 2020) - Chakraborty, Papiya; Dalpati, Nibedita; Bhan, Chandra; Dash, Shiba Prasad; Kumar, Puneet; Sarangi, Pranita P.
Highlights: Fbln7-C binds to integrin β1 on neutrophils and reduce adhesion and migration. Fbln7-C reduces cytokine and ROS production from activated neutrophils. Fbln7-C improves survival of endotoxemic mice. Abstract: Accumulation of hyperactive neutrophils in the visceral organs was shown to be associated with sepsis-induced multi-organ failure. Recently, a C-terminal fragment of secreted glycoprotein Fibulin7 (Fbln7-C) was shown to inhibit angiogenesis and regulate monocyte functions in inflammatory conditions. However, its effects on neutrophil functions and systemic inflammation induced lethality remain unknown. In this study, we show that human peripheral blood neutrophils adhered to Fbln7-C in a dose-dependent manner via integrin β1. Moreover, the presence of Fbln7-C inhibited spreading, and fMLP mediated random migration of neutrophils on fibronectin. Significant reduction in ROS and inflammatory cytokine production (i.e., IL-6, IL-1β) was observed, including a reduction in ERK1⁄2 phosphorylation in neutrophils stimulated with LPS and fMLP in the presence of Fbln7-C compared to untreated controls. In an in vivo model of endotoxemia, the administration of Fbln7-C (10 μg/dose) significantly improved survival and reduced the infiltration of neutrophils to the site of inflammation. Additionally, neutrophils infiltrating into the inflamed peritoneum of Fbln7-C administered animals expressed lower levels CD11b marker, IL-6, and produced lower levels of ROS upon stimulation with PMA compared to untreated controls. In conclusion, our results show that Fbln7-C could bind to the integrin β1 on the neutrophil surface and regulate their inflammatory functions.